2010
DOI: 10.1021/la102106t
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Cholic Acid and Dodecylphosphocholine−Cholic Acid Aggregates

Abstract: Bile acids are powerful detergents that emulsify and solubilize lipids, vitamins, cholesterol and other molecules in the biliary tract and intestines. It has long been known that bile acids form soluble mixed micelles with lipids. However, the detailed thermodynamic and structural properties of these micelles are not fully understood. This study sheds light on this issue based on results from multiple molecular dynamics simulations of cholic acid (CA) and dodecylphosphocholine (DPC) mixed micelles. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 44 publications
12
39
0
Order By: Relevance
“…Subsequent studies [42,43] found features of a disk-shaped micelle originally proposed by Carey and Small [44]. Our own previous study on pure cholic acid (CA) and CA-dodecylphosphocholine (DPC) micelles supported the radial-shell model and revealed a linear dependence of micelle size on CA concentration [45]. …”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Subsequent studies [42,43] found features of a disk-shaped micelle originally proposed by Carey and Small [44]. Our own previous study on pure cholic acid (CA) and CA-dodecylphosphocholine (DPC) micelles supported the radial-shell model and revealed a linear dependence of micelle size on CA concentration [45]. …”
Section: Introductionmentioning
confidence: 75%
“…The stability of the simulations was monitored by the time evolution of the number of CA or IBU monomers (N Monomers ), as well as the weight and number averaged aggregation numbers N W and N N (Figure S3). N W and N N , as well as principal moments of inertia I 1 , I 2 and I 3 , were calculated as described before [45]. The weighted probability distribution (P n ) of micelles and monomers was calculated as: Pn=XN where X=(F=1NFnCSn)NF. CSn is the number of CA-IBU mixed-micelles of size n ( n =2, 3, 4…) or the number of CA and IBU monomers ( n = 1), F is frame index, N F is the total number of frames sampled every 10ps and N the total number of CA and IBU molecules in the system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular dynamics simulations at the mesoscale are the most indicated tool to address the issues discussed in the main text. It is interesting to note that only limited surfactants phase diagram regions have been generally considered in the literature, focusing particularly on micellar phases [30][31][32][33] , in high hydration conditions. These works mostly report phase diagrams and basic structural details, in the form of pair distribution functions and typical sizes of surfactant clusters.…”
Section: Methodsmentioning
confidence: 99%